3D-printed brace in the treatment of adolescent idiopathic scoliosis: a study protocol of a prospective randomised controlled trial. Issue 11 (27th November 2020) - Zhang, Youyu; Liang, Junyang; Xu, Nanfang; Zeng, Lin; Du, Chaojun; Du, Yaoxu; Zeng, Yan; Yu, Miao; Liu, Zhongjun
Abstract : Introduction: Adolescent idiopathic scoliosis (AIS) is a three-dimensional deformity of the spine. Brace treatment is effective for eligible patients with AIS and the effectiveness is significantly correlated with the average brace-wear time per day. Three-dimensional (3D) printing technology is a recent advancement that offers unique opportunities for biomedical applications, and customisation of scoliosis braces might lead to greater patient satisfaction and improved compliance. We present here the design of a randomised controlled trial on the clinical effectiveness of 3D-printed braces versus thoracolumbosacral orthoses (TLSO) for patients with AIS. Methods and analysis: Patients with AIS (age 10–16 years) with Risser sign 0-II, Cobb angle of main curve of 20°−40°, premenarchal or no more than 1-year postmenarchal (for women), and no history of treatment are eligible, unless they are unable to tolerate the treatment or refuse participation. A total of 88 patients will be randomised into either the 3D group or TLSO group on a 1:1 basis. Participants in the 3D group will choose between a 3D-printed brace and TLSO, according to the Zelen's design of the trial. Primary outcome measures will include the average brace-wear time per day, health-related quality of life and Cobb angle progression of the primary curve. Secondary outcome measures will include immediate in-brace correction of Cobb angle of the primary curve, rate of conversion to surgery and incidence of any adverse events. This study is designed as a single-centre, two-arm, superiority and open-label randomised controlled trial. The sample size is calculated with reference to the preliminary study and based on the sample size calculation formula. Ethics and dissemination: This study was approved by the Peking University Third Hospital Medicine Science Research Ethics Committee (No: 2019-017-02). Results of the trial will be submitted for publication in a peer-reviewed journal and as conference presentations. Trial registration number: ChiCTR1900027379, pre-results.